2006
DOI: 10.1002/ppul.20488
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of oropharyngeal dysphagia in children without apparent risk factors

Abstract: : Oropharyngeal dysphagia should be considered in the differential diagnosis of young children without known risk factors associated with swallowing dysfunction when they present with unexplained respiratory problems. Although the prognosis for resolution of dysphagic concerns is very good, it may take several years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 18 publications
6
83
1
5
Order By: Relevance
“…aspiration-induced lung disease, malnutrition, neurodevelopmental problems, sensory-based feeding disorder, and/or disruption of normal child-family bonding [1]. The feeding and swallowing literature from decades ago to the present consistently recognizes a correlation between swallowing and physical characteristics of food.…”
mentioning
confidence: 99%
“…aspiration-induced lung disease, malnutrition, neurodevelopmental problems, sensory-based feeding disorder, and/or disruption of normal child-family bonding [1]. The feeding and swallowing literature from decades ago to the present consistently recognizes a correlation between swallowing and physical characteristics of food.…”
mentioning
confidence: 99%
“…In a study of children without known dysphagia risk factors who demonstrated unexplained respiratory problems [14], almost 60% were found to aspirate liquids and, of these, 100% of aspiration events were silent (i.e. no cough).…”
Section: Dysphagia and Aspiration In Pediatric Populationsmentioning
confidence: 99%
“…Several studies indicate that, although the prognosis for resolution of pediatric dysphagia is often very good, it might take several years [60,61]. …”
Section: Management Of Pediatric Swallowing Disordersmentioning
confidence: 99%
“…Children with respiratory problems may present swallowing alterations, which can be observed in videofluoroscopic evaluation (22,(24)(25)(26) . According to some authors, swallowing disorders are frequently observed in infants with history of bronchitis and/or recurrent pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the delay always preceded penetration or laryngeal aspiration, and all aspirations were silent. Hence, oropharyngeal disphagia must be considered in the differential diagnosis of this population (26) . In infants with severe neurological disorders, alterations in oral and pharyngeal phases of swallowing, which result in aspiration, are the main cause of respiratory infections (11) .…”
Section: Introductionmentioning
confidence: 99%